Impact of Vitamin D Supplementation on Influenza Vaccine Response and Immune Functions in Deficient Elderly Persons: A Randomized Placebo-Controlled Trial - Goncalves-Mendes, Nicolas; Talvas, Jérémie; Dualé, Christian; Guttmann, Aline; Corbin, Violaine; Marceau, Geoffroy; Sapin, Vincent; Brachet, Patrick; Evrard, Bertrand; Laurichesse, Henri; Vasson, Marie-Paule (Frontiers in Immunology, 2019)
Background: Immunosenescence contributes to reduced vaccine response in elderly persons, and is worsened by deficiencies in nutrients such as Vitamin (Vit-D). The immune system is a well-known target of Vit-D, which can both potentiate the innate immune response and inhibit the adaptive system, and so modulate vaccination response. Objective: This randomized placebo-controlled double-blind trial investigated whether Vit-D supplementation in deficient elderly persons could improve influenza seroprotection and immune response. Design: Deficient volunteers (Vit-D serum < 30 ng/mL) were assigned (V1) to receive either 100,000 IU/15 days of cholecalciferol (D, n = 19), or a placebo (P, n = 19), over a three month period. Influenza vaccination was performed at the end of this period (V2), and the vaccine response was evaluated 28 days later (V3). At each visit, serum cathelicidin, immune response to vaccination, plasma cytokines, lymphocyte phenotyping and phagocyte ROS production were assessed. Results: Levels of serum 25-(OH)D increased after supplementation (D group, V1 vs V2: 20.7 ± 5.7 vs 44.3 ± 8.6 ng/mL, p < 0.001). No difference was observed for serum cathelicidin levels, antibody titers and ROS production in D vs P groups at V3. Lower plasma levels of TNFα (p = 0.040) and IL-6 (p = 0.046), and higher ones for TFGβ (p = 0.0028) were observed at V3. The Th1/Th2 ratio was lower in the D group at V2 (D: 0.12 ± 0.05 vs P: 0.18 ± 0.05, p = 0.039). Conclusions: Vit-D supplementation promotes a higher TGFβ plasma level in response to influenza vaccination without improving antibody production. This supplementation seems to direct the lymphocyte polarization towards a tolerogenic immune response. A deeper characterization of metabolic and molecular pathways of these observations will aid in the understanding of Vit-D's effects on cell-mediated immunity in aging. This clinical trial was registered at clinicaltrials.gov as NCT01893385.